A rule-based expert system applied to moisture durability of building envelopes. (November 2018) - Boudreaux, Philip; Pallin, Simon; Accawi, Gina; Desjarlais, Andre; Jackson, Roderick; Senecal, David
The moisture durability of an envelope component such as a wall or roof is difficult to predict. Moisture durability depends on all the construction materials used, as well as the climate, orientation, air tightness, and indoor conditions. Modern building codes require more insulation and tighter construction but provide little guidance about how to ensure these energy-efficient assemblies remain moisture durable. Furthermore, as new products and materials are introduced, builders are increasingly uncertain about the long-term durability of their building envelope designs. Oak Ridge National Laboratory and the US Department of Energy's Building America Program are applying a rule-based expert system methodology in a web tool to help designers determine whether a given wall design is likely to be moisture durable and provide expert guidance on moisture risk management specific to a wall design and climate. The expert system is populated with knowledge from both expert judgment and probabilistic hygrothermal simulation results.